2013
DOI: 10.1007/s10029-013-1177-5
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of inguinal hernia epidemiology adjusted for population age structure in Tanzania

Abstract: Our data indicate the extent of inguinal hernia disease burden in Tanzania. By adjusting our figures for the age structure of Tanzania, we have demonstrated that while the incidence of symptomatic cases may be lower than previously thought, prevalence of inguinal hernia in Tanzania remains high. This approach provides an update to our previously described methodology for calculation of inguinal hernia epidemiology in resource-poor settings that may be used in multiple country contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…[19] Similarly, operative record and communitybased studies form sub-Saharan Africa, Taiwan, United States, Israel and Brazil reported prevalence between 2.4 -7.9%, all of which greater than the prevalence reported in Nepal. [1,[20][21][22][23][24][25] The burden of untreated hernias in South Asia has not previously been reported for comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Similarly, operative record and communitybased studies form sub-Saharan Africa, Taiwan, United States, Israel and Brazil reported prevalence between 2.4 -7.9%, all of which greater than the prevalence reported in Nepal. [1,[20][21][22][23][24][25] The burden of untreated hernias in South Asia has not previously been reported for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…[1] However, low-and middle-income countries (LMICs) are universally ill equipped to care for common surgical diseases. [2][3][4] Subsequently, there is a large unmet need for inguinal herniorrhaphy.…”
Section: Introductionmentioning
confidence: 99%
“…The recently published studies on the cost-effectiveness of hernia repair in disadvantaged countries [15,24,27,34] may represent a solution for the health policy of these countries when choosing the most costeffective procedure for hernia repair.…”
Section: Discussionmentioning
confidence: 98%
“…В Танзании в 2013 г. для оценки эпидемиологиче-ских данных за основу взяты данные United States National Health and Nutrition Examination Survey (NHANES), которые были экстраполированы на население Танзании. В результате сделан вывод о том, что паховая грыжа встречается у 12% мужчин [8]. В Гане в то же самое время распространенность паховых грыж составила 3,15% [2].…”
Section: результаты и обсуждениеunclassified